Assessment of Production Processes Functioning in Enterprises from Metal Industry - Krzysztof MIELCZAREK (Communications of International Proceedings, 2021)
An innovative BOST questionnaire survey was characterized as a tool for transformation of Toyota's management principles into the questions. Survey questions from BOST study were described, which are used in evaluation of production process and its elements with reference to second and third Toyota's management principle (question E3 and E4). Research group which participated in BOST study from the metal industry was characterized.  Analysis of the research results was presented in the form of tables, histograms, radar chart and some statistical tools. The aim of the analysis is to present which factors are the most important by building the significance sequences of obtained results. The results obtained for the type of small and medium-sized enterprises overlap with the results of tests verified in other enterprises.
Keywords: BOST Method; Improvement; Toyota Management Principle; Statistical Analysis; Importance Hierarchy